Induction of protective interferon-β responses in murine osteoblasts following Staphylococcus aureus infection - Johnson, M. Brittany; Furr, Kelli H.; Suptela, Samantha R.; Leach, Whitney; Marriott, Ian (Frontiers in Microbiology, 2022)
The refractory and recurrent nature of chronic staphylococcal osteomyelitis may be due, at least in part, to the ability of Staphylococcus aureus to invade and persist within bone-forming osteoblasts. However, osteoblasts are now recognized to respond to S. aureus infection to produce numerous immune mediators and bone regulatory factors that can shape the host response. Type I interferons (IFNs) are best known for their antiviral effects, but it is becoming apparent that they impact host susceptibility to a wide range of pathogens including S. aureus. Here, we report the presence of markedly elevated IFN-beta levels in infected bone tissue in a mouse model of staphylococcal osteomyelitis. RNA Tag-Seq analysis of S. aureus infected primary murine osteoblasts showed enrichment of genes associated with type I IFN signaling and IFN stimulated genes (ISGs), and elevated expression of mRNA encoding IFN-beta and ISG products. IFN-beta production was confirmed with the demonstration that S. aureus induces its rapid and robust release by osteoblasts in a dose-dependent manner. Furthermore, we show increased protein expression of the ISG products IFIT1 and IFIT3 by infected osteoblasts and demonstrate that this occurs secondary to the release of IFN-beta by these cells. Finally, we have determined that exposure of S. aureus-infected osteoblasts to IFN-beta markedly reduces the number of viable bacteria harbored by these cells. Together, these findings indicate an ability of osteoblasts to respond to bacteria by producing IFN-beta that can act in an autocrine and/or paracrine manner to elicit ISG expression and mitigate S. aureus infection.